The interpersonal communication book - De Vito, Joseph A.; Pearson Education Limited (United Kingdom Pearson Education Limited, 2022)
The Interpersonal Communication Book balances theory and research with explication of practical skills to provide students with an in-depth understanding of interpersonal communication. With the concept of choice as its philosophical foundation, the book uses a threefold approach to assess communication: it examines the choices that are present in interpersonal situations, explains the theory and research that relates to these choices and provides the skills necessary to create effective messages.

Keeping pace with important recent events, the sixteenth edition incorporates the implications of the Black Lives matter movement and the COVID-19 pandemic throughout its narrative. This edition also includes extensive revisions to accurately present the most up-to-date knowledge about interpersonal communication.
Includes references (pages [390]-419) and index (pages 422-430).
Keywords: Interpersonal communication .; Sociology